Revolusi Digital dan Merdeka Belajar: Meningkatkan Daya Saing Siswa di Era Teknologi - Fahrina Yustiasari Liriwati (STIKes Ibnu Sina Ajibarang, 2023)
The digital revolution has fundamentally changed the educational paradigm, influencing the way of learning, teaching and interacting in the educational environment. In responding to the challenges and opportunities presented by this technological era, the concept of